Hantavirus Associated with Hemorrhagic Fever with Renal Syndrome Outbreak in the Saratov Region in 2019 - L. N. Yashina; T. V. Tregubchak; B. S. Malyshev; N. A. Smetannikova; I. V. Grishchenko; A. A. Dol’sky; A. N. Shvalov; A. V. Zaykovskaya; A. V. Kazantsev; V. N. Chekashov; T. Yu. Krasovskaya (Проблемы особо опасных инфекций)
Pathogenic hantaviruses, belonging to the family Hantaviridae, genus Orthohantavirus, are widely spread in many regions of the world and cause hemorrhagic fever with renal syndrome (HFRS) in Europe and Asia. In the European Russia, the most active HFRS foci are located in the optimum habitat area of natural reservoir of the Puumala virus (PUUV), bank voles (Myodes glareolus), – in the Middle Volga and Cis-Urals. The largest number of cases of HFRS was registered in the Volga Federal District. In 2019, an outbreak of HFRS was registered among the residents of Saratov and the Saratov Region, the number of cases was 2702. Objective of the study was genetic identification of hantaviruses from HFRS patients and rodent carriers and phylogenetic analysis of full-size genomes from natural hosts during HFRS outbreak in the Saratov Region, 2019. Materials and methods. Blood samples of 8 HFRS patients from Saratov and 3 lung samples of bank voles captured in the suburb of Saratov were analyzed using reverse transcription polymerase chain reaction, followed by sequencing and phylogenetic analysis. Results and discussion. A total of 6 viral RNA isolates from HFRS patients were genetically typed, full-length RNA-isolate genomes were obtained for 3 natural carriers. Our data indicate that PUUV virus was associated with HFRS outbreak in Saratov. Genetic analysis revealed that the virus belonged to RUS lineage of PUUV, related most closely to strains from Udmurtia and Tatarstan and differed from strains circulating in the territory of Bashkortostan and Samara Region.